When Do We Stop Asking ‘Why’?: Exploring the Possibilities and Challenges of Collective Critical Reflection for Staff and Organizational Development - Margo J. Hittleman (Adult Education Research Conference, 2007)
This study of an organization-wide process of collective critical reflection discusses the challenges and possibilities that the staff of a multi-cultural community center faced as they attempted to not only reflect on, but collectively respond to contesting perspectives on their work within social environments shaped by institutionalized relations of power.